Analisis Penyaluran Kredit Usaha Rakyat (KUR) Pada UMKM di Bolu Pada Bank BRI - Jesy Likubanne Mallisa’; Mince Batara; Rati Pundissing (STIKes Ibnu Sina Ajibarang, 2023)
The population and at the same time being the sample in this study are the debtors of Bank BRI Unit Bolu. Then the sampling to obtain information about the objects of this research is by means of homogeneous sampling in which the elements of the population studied have properties that are relatively uniform to one another. The samples taken in this study were 50 debtors. This study uses a quantitative descriptive approach in the form of questionnaires to debtors about credit granting procedures. Data collection techniques used were interviews, observations, and questionnaires. Data analysis techniques used are data percentage, data reduction, and data descriptive. The results showed that from the 5C assessment at Bank BRI Unit Bolu, it could be concluded that the distribution of People's Business Credit (KUR) was fully in accordance with the standards set by Bank BRI Unit Bolu, which can be seen from the results of the questionnaire obtained from 50 customers who were at a percentage value of 70% - 100%.